2000
DOI: 10.1128/aac.44.9.2452-2457.2000
|View full text |Cite
|
Sign up to set email alerts
|

Astaxanthin-Rich Algal Meal and Vitamin C Inhibit Helicobacter pylori Infection in BALB/cA Mice

Abstract: Helicobacter pylori infection in humans is associated with chronic type B gastritis, peptic ulcer disease, and gastric carcinoma. A high intake of carotenoids and vitamin C has been proposed to prevent development of gastric malignancies. The aim of this study was to explore if the microalga Haematococcus pluvialis rich in the carotenoid astaxanthin and vitamin C can inhibit experimental H. pylori infection in a BALB/cA mouse model. Six-week-old BALB/cA mice were infected with the mouse-passaged H. pylori stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
2
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(99 citation statements)
references
References 38 publications
3
93
2
1
Order By: Relevance
“…A doctor's interview was conducted prior to blood sampling before (0) and 4,6,8,24,72, and 168 h after astaxanthin administration. All serum samples were prepared by centrifugation (4 C, 2,500 rpm, 5 min) from the blood quickly after sampling, and were stored in a freezer (À20 C) until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A doctor's interview was conducted prior to blood sampling before (0) and 4,6,8,24,72, and 168 h after astaxanthin administration. All serum samples were prepared by centrifugation (4 C, 2,500 rpm, 5 min) from the blood quickly after sampling, and were stored in a freezer (À20 C) until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…4) Due to their high antioxidant properties, many nutraceuticals containing astaxanthin have potent effects against many symptoms and are coming onto the market. Recently, further functionalities of astaxanthin in addition to its antioxidative ability have also been reported, including anti-cancer, 5,6) prevention of diabetic nephropathy, 7) prevention of H. pylori infection, 8) alleviation of eye fatigue, 9) and immunomodulating ability. 10,11) Absorption of xanthophylls is believed to occur as follows: After ingestion, xanthophylls mix with bile acid to make micelles in the intestinum tenue.…”
mentioning
confidence: 99%
“…198 Vitamin C is not only an antioxidant and a free radical scavenger but it also shows antimicrobial activity both in vitro and in vivo, 192 and is able to inhibit H. pylori growth in vitro. 199,200 Several investigators 201,202 have…”
Section: Helicobacter Pylorimentioning
confidence: 99%
“…Of the potential novel non-antibiotic treatment strategies, anti-adhesive compounds to inhibit tissue invasion by bacterial pathogens are promising candidates [13,14]. This group of investigators has previously standardised a mouse model for H. pylori infection [15±17] and recently reported that antioxidants such as astaxanthin and vitamin C inhibit H. pylori infection in this model [18]. The present study investigated whether bovine milk glycoproteins could inhibit an experimental H. pylori infection in a BALB=cA mouse model, to develop a possible anti-adhesion strategy in the future.…”
Section: Introductionmentioning
confidence: 99%